Ischemia Reperfusion Injury Significantly Differs between Lung vs. Heart Transplantation with Respect to Lead Cytokines and Correlation to Clinical Outcome. (July 2018) - Wiegmann, Bettina; Ledwoch, Nadine; Iske, Jasper; Kaufeld, Tim; Ius, Fabio; Rochas, Sebastian; Avsar, Murat; Haverich, Axel; Warnecke, Gregor; Falk, Christine S
Abstract : Objectives : Ischemia reperfusion injury (IRI) is known to impair early graft function after lung (LTx) or heart (HTx) transplantation. We have previously characterized IRI in recipients of lungs preserved by standard cold storage by a peak response directly after Tx. The lead cytokines involved in IRI after LTx were, amongst others, IL-6, CXCL8, CCL2. Since organ-specific aspects of IRI are not well understood, we aimed to define IRI in HTx and to identify differences with respect to this peak cytokine/chemokine response. Methods: Plasma samples of LTx or HTx recipients were analysed preTx, at T0, T24, as well as respective perfusion solutions. 26 LTx recipients (mean age 49y) and 13 HTX recipients (mean age 47y) were included into the study. Protein concentrations of 99 cytokines, chemokines, angiogenic factors were determined using multiplex assays. Clinical data, i.e. cold ischemic time (CIT), immunosuppression etc. were also collected. Principal component (PCA), unsupervised cluster and K-network classifier (KNN) analyses were performed for the identification of the lead factors of IRI in LTx vs. HTx. Results: KNN, unsupervised cluster and PCA analyses identified IL-6 as strongest signal for IRI in LTx recipients (preTx/T0 p<0.001) and high IL-6 levels correlated with PGD>2, CIT and PaO2/FiO2 ratio. In contrast, IL-10 was leading in HTx (preTx/T0 p<0.001), being sufficient to discriminate between preTx and T0 plasma samples on its own. Advanced statistics of LTx samples identified IL-10, IGFBP1, CXCL8, G-SCF, HGF and IL-16 (all p<0.01) as top discriminators. The overlap to HTx samples comprises IGFBP1, IL-16 (all p<0.001), but of note, not IL-6. Instead, SCGF, M-CSF, VCAM, sVEGFR1, and the Tie2/Ang-2 and PAI-1/uPA ratios (all p<0.001) dominated the IRI response in HTx patients. These differences were also observed in perfusion solutions of hearts vs. lungs after standard cold preservation (all p<0.001). Conclusion: The comparison of soluble immune mediators in plasma of lung vs. heart recipients revealed significant differences in IRI response, especially regarding the lead cytokines IL-6 and IL-10. These differences are likely to reflect organ-specific components in IRI. Thus, different biomarker candidates may be useful for the quantification of IRI in lung vs. heart transplant patients. IFB-Tx OPEX_2. SFB738, B3.